2018
DOI: 10.1016/j.immuni.2018.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 Directly Inhibits CD8+ T Cell Function by Enhancing N-Glycan Branching to Decrease Antigen Sensitivity

Abstract: Chronic viral infections remain a global health concern. The early events that facilitate viral persistence have been linked to the activity of the immunoregulatory cytokine IL-10. However, the mechanisms by which IL-10 facilitates the establishment of chronic infection are not fully understood. Herein, we demonstrated that the antigen sensitivity of CD8 T cells was decreased during chronic infection and that this was directly mediated by IL-10. Mechanistically, we showed that IL-10 induced the expression of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
167
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(181 citation statements)
references
References 56 publications
2
167
1
1
Order By: Relevance
“…In the context of influenza infection, however, the role of IL-10 still remains controversial as the genetic background appears to have a dominant effect on disease susceptibility 59,60 . More recently, Smith et al demonstrated that IL-10 can act directly on CD8 + T cells by increasing the antigenic threshold for T cell activation and that this process was highly dependent on the dose and timing of exposure 17 . Since the impact of IL-10 is clearly determined by the timing and site of its production, TIGIT modulation might be used as a surrogate to generate a local immune suppressive environment at sites of tissue inflammation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the context of influenza infection, however, the role of IL-10 still remains controversial as the genetic background appears to have a dominant effect on disease susceptibility 59,60 . More recently, Smith et al demonstrated that IL-10 can act directly on CD8 + T cells by increasing the antigenic threshold for T cell activation and that this process was highly dependent on the dose and timing of exposure 17 . Since the impact of IL-10 is clearly determined by the timing and site of its production, TIGIT modulation might be used as a surrogate to generate a local immune suppressive environment at sites of tissue inflammation.…”
Section: Discussionmentioning
confidence: 94%
“…Importantly, loss of TIGIT results in hyperproliferative and inflammatory T cell responses and a marked reduction in IL-10 9,14 . IL-10 itself is a key regulator of immune responses during infections, where it plays a two-sided role by both promoting pathogen persistence [17][18][19] as well as limiting excessive Th1 and CD8 + T cell responses that cause immune pathology 20,21 . Incidentally, many chronic or latent human viruses have evolved to encode IL-10 homologs in order to evade immune control 22 .…”
mentioning
confidence: 99%
“…Though the overall number of CD8+ effector T cells in the brain is not increased, we still observed an increased frequency of Ki67+ CD8+ T cells in the brain after IL-10R blockade, suggesting that this population is still responsive to IL-10-mediated suppression; perhaps through an intrinsic response to IL-10 that limits their proliferative capacity. IL-10 has been shown to be able to directly inhibit proliferation of CD8+ T cells in vitro [14], as well as control the threshold of their response to antigen upon initial activation [68]. Much is still unknown about the direct effects of IL-10 on activated CD8+ T cells that could contribute to their regulation, though these data further suggest that CD8+ effector T cells may be differentially regulated from the CD4+ effector T cell compartment in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…IL10 is shown to suppress innate and adaptive immune responses, mediate tissue repair, and maintain epithelium integrity [17]. In addition, IL10 can directly dampen the signal transduction of CD8 T cells, thus increasing the threshold required for antigen recognition and activation [18]. Interestingly, polymorphisms that increase IL10 production are associated with elevated GC risk [19][20][21], which is contrary to the hypothesis that IL10 may prevent inflammation-induced disruption of the epithelium.…”
Section: Introductionmentioning
confidence: 94%